2018
DOI: 10.1093/heapol/czx167
|View full text |Cite
|
Sign up to set email alerts
|

Examining clinical leadership in Kenyan public hospitals through the distributed leadership lens

Abstract: Clinical leadership is recognized as a crucial element in health system strengthening and health policy globally yet it has received relatively little attention in low and middle income countries (LMICs). Moreover, analyses of clinical leadership tend to focus on senior-level individual leaders, overlooking a wider constellation of middle-level leaders delivering health care in practice in a way affected by their health care context. Using the theoretical lens of ‘distributed leadership’, this article examines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 52 publications
(80 reference statements)
2
51
1
1
Order By: Relevance
“…It could also consider the value of "distributed leadership" in advancing change. Nzinga, McGivern, and English (2018) utilize distributed leadership in the context of leadership in health systems (clinical leadership) in Kenya. Distributed leadership "provides a holistic sense to leadership as a product of leaders and followers co-constructing performance in collective and group context, and provides a dynamic, nonlinear frame on how people and events interact in organizations" (Nzinga, McGivern, & English, 2018, p. ii28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It could also consider the value of "distributed leadership" in advancing change. Nzinga, McGivern, and English (2018) utilize distributed leadership in the context of leadership in health systems (clinical leadership) in Kenya. Distributed leadership "provides a holistic sense to leadership as a product of leaders and followers co-constructing performance in collective and group context, and provides a dynamic, nonlinear frame on how people and events interact in organizations" (Nzinga, McGivern, & English, 2018, p. ii28).…”
Section: Discussionmentioning
confidence: 99%
“…Distributed leadership "provides a holistic sense to leadership as a product of leaders and followers co-constructing performance in collective and group context, and provides a dynamic, nonlinear frame on how people and events interact in organizations" (Nzinga, McGivern, & English, 2018, p. ii28). Nzinga et al (2018) provide insights into the value of soft skills for doctors in leadership roles. Importantly, their work demonstrated the power of distributed leadership in bringing about change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing two urban district hospitals in Ghana, one with specialist services and one without, Aberese-Ako et al (2018) explore what strategies managers working at all levels of the hospitals used to cope with the contextual constraints they faced. In Kenya, meanwhile, Nzinga et al (2018) working in two county (district) hospitals, reveal the individualized decision-making and often intimidatory leadership practices of mid-level managers, the clinical heads and nurses in charge of inpatient wards.…”
Section: What Do the Papers Presented Here Consider?mentioning
confidence: 99%
“…In Kenya, a study conducted by Nzinga, McGivern, and English (2018) showed that most departments are headed by surgeons or senior doctors who are highly trained in the medical area but exhibit but have little training on leadership. These leaders exhibit unfamiliarity with leadership and organizational behaviour techniques because of inadequate on-the-job leadership and management training courses, and in many cases, managers' disbelief in the effectiveness and necessity of learning these techniques.…”
mentioning
confidence: 99%